Superconductivity and normal state properties of non-centrosymmetric CePt₃Si: a status report - Bauer, E.; Bonalde, I.; Sigrist, M. (Физика низких температур, 2005)
Ternary CePt₃Si crystallizes in the tetragonal P4mm structure which lacks a center of inversion. Antiferromagnetic order sets in at TN≈22 . K followed by superconductivity (SC) below Tc≈ 0.75 K. Large values of H'c2≈-8.5 T/K and Hc2(0)≈5T were derived, referring to Cooper pairs formed out of heavy quasiparticles. The mass enhancement originates from Kondo interactions with a characteristic temperature TK≈ 8 K. CePt₃Si follows the general features of correlated electron systems and can be arranged within the Kadowaki–Woods plot next to the unconventional SC UPt₃. NMR and mSR results show that both magnetic order and SC coexist on a microscopic scale without having spatial segregation of both phenomena. The absence of an inversion symmetry gives rise to a lifting of the degeneracy of electronic bands by spin-orbit coupling. As a consequence, the SC order parameter may have uncommon features as indicated from a very unique NMR relaxation rate 1/T₁ and a linear temperature dependence of the penetration depth λ.